Development of a conceptual framework to guide description and evaluation of social interventions for people with serious mental health conditions - Rebecca Appleton; Phoebe Barnett; Beverley Chipp; Michael Clark; Peter Goldblatt; Stephen Jeffreys; Karen Machin; Justin J. Needle; Prisha Shah; Georgina Thompson; Kylee Trevillion; Martin Webber; et al. (Elsevier, 2023)
People with serious mental health conditions face social exclusion and have poorer social outcomes compared to the general population in several areas of life. Social exclusion also negatively impacts mental health. Promising models of support to improve social outcomes for people with serious mental health conditions have been described in the literature and proliferate in practice, but typologies of support are not clearly established and a robust evidence base for effective approaches is lacking in many areas. We conducted a scoping review of relevant literature and consulted with experts in the field to identify models to improve social circumstances across eight life domains, with the aim of developing a conceptual framework to distinguish the main broad approaches to improving the social circumstances of people with serious mental health conditions. We also sought to explore which approaches have been used in models within each life domain. This work was conducted in collaboration with a group of expert stakeholders, including people with lived experience of accessing mental health services. We developed a conceptual framework which distinguishes sources and types of support, allowing description of complex interventions to improve the social circumstances of people with serious mental health problems, and providing a framework to guide future service development and evaluation.